2018
DOI: 10.7554/elife.37703
|View full text |Cite
|
Sign up to set email alerts
|

TrpV1 receptor activation rescues neuronal function and network gamma oscillations from Aβ-induced impairment in mouse hippocampus in vitro

Abstract: Amyloid-β peptide (Aβ) forms plaques in Alzheimer’s disease (AD) and is responsible for early cognitive deficits in AD patients. Advancing cognitive decline is accompanied by progressive impairment of cognition-relevant EEG patterns such as gamma oscillations. The endocannabinoid anandamide, a TrpV1-receptor agonist, reverses hippocampal damage and memory impairment in rodents and protects neurons from Aβ-induced cytotoxic effects. Here, we investigate a restorative role of TrpV1-receptor activation against Aβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(127 citation statements)
references
References 68 publications
10
117
0
Order By: Relevance
“…Recent evidence shows widespread TRPV1 expression in the central nervous system (CNS) tissues, including the cortex, hippocampus, hypothalamus, and retina (Mezey et al, 2000;Roberts et al, 2004;Cristino et al, 2006;Sappington et al, 2009Sappington et al, , 2015Jo et al, 2017;Lakk et al, 2018). TRPV1 has also been implicated in neurodegenerative disorders such as Alzheimer's disease (Jayant et al, 2016;Balleza-Tapia et al, 2018), Parkinson's disease (Marinelli et al, 2003;Morgese et al, 2007;Nam et al, 2015;Chung et al, 2017), Huntington's disease (Lastres-Becker et al, 2003), and glaucomatous optic neuropathy, or glaucoma (Ward et al, 2014;Weitlauf et al, 2014). Glaucoma is the leading cause of irreversible blindness (Quigley and Broman, 2006), involving sensitivity to intraocular pressure (IOP) that stresses retinal ganglion cell (RGC) axons as they form the optic nerve (Calkins, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence shows widespread TRPV1 expression in the central nervous system (CNS) tissues, including the cortex, hippocampus, hypothalamus, and retina (Mezey et al, 2000;Roberts et al, 2004;Cristino et al, 2006;Sappington et al, 2009Sappington et al, , 2015Jo et al, 2017;Lakk et al, 2018). TRPV1 has also been implicated in neurodegenerative disorders such as Alzheimer's disease (Jayant et al, 2016;Balleza-Tapia et al, 2018), Parkinson's disease (Marinelli et al, 2003;Morgese et al, 2007;Nam et al, 2015;Chung et al, 2017), Huntington's disease (Lastres-Becker et al, 2003), and glaucomatous optic neuropathy, or glaucoma (Ward et al, 2014;Weitlauf et al, 2014). Glaucoma is the leading cause of irreversible blindness (Quigley and Broman, 2006), involving sensitivity to intraocular pressure (IOP) that stresses retinal ganglion cell (RGC) axons as they form the optic nerve (Calkins, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cell damage is attenuated by an intracellular Ca 2+ -chelator. In a recent study, the activity of TRPV1 was reported to decrease Aβ-induced cytotoxicity (Balleza-Tapia et al, 2018). Treatment with a TRPV1 agonist rescued Aβ-induced degradation of hippocampal neuron function (Figure 2A).…”
Section: Trpv1mentioning
confidence: 71%
“…TRPM2 expression is involved in synapse loss, microglial activation, and spatial memory deficits in APP/PS1 mice (Ostapchenko et al, 2015). Activation of TRPV1 channels is required to trigger longterm depression at interneuronal synapses (Gibson et al, 2008) and prevents Aβ-involved impairment of functional networks in the hippocampus (Balleza-Tapia et al, 2018). Astrocytic Ca 2+ hyperactivity is induced by Aβ oligomers via TRPA1 in the hippocampus.…”
Section: Trp Channels: Novel Therapeutic Candidate For Neurodegeneratmentioning
confidence: 99%
“…Direct application of Aβ can disrupt spontaneous oscillatory network activity in vitro (Adaya‐Villanueva, Ordaz, Balleza‐Tapia, Márquez‐Ramos, & Peña‐Ortega, ; Balleza‐Tapia, Huanosta‐Gutiérrez, Márquez‐Ramos, Arias, & Peña, ; Gutiérrez‐Lerma, Ordaz, & Peña‐Ortega, ; Peña et al, ; Peña‐Ortega, Solis‐Cisneros, Ordaz, Balleza‐Tapia, & Javier, ) and in vivo (Colom et al, ; Cornejo‐Montes‐de‐Oca, Hernández‐Soto, Isla, Morado‐Urbina, & Peña‐Ortega, ; Peña‐Ortega & Bernal‐Pedraza, ; Villette et al, ). The cellular mechanisms involved in Aβ‐induced disruption of neural network activity comprise changes in synaptic transmission (Balleza‐Tapia et al, ; Mura et al, ; Peña et al, ; Salamone et al, ; Satoh et al, ) and in intrinsic neuronal properties (Chen, ; Hou, Cui, Yu, & Zhang, ; Mondragón‐Rodríguez, Gu, et al, ; Peña et al, ; Rovira, Arbez, & Mariani, ; Shankar & Walsh, ; Ye, Selkoe, & Hartley, ), which involve direct actions of Aβ on ion channels (Balleza‐Tapia et al, ; Chen, ; Hou et al, ; Rovira et al, ; Shankar & Walsh, ; Ye et al, ) and/or their modulation through the activation of intracellular transduction pathways (Ekinci, Malik, & Shea, ; Wildburger & Laezza, ; Zhu et al, ). At the synaptic level, Aβ produces alterations at both presynaptic (Balleza‐Tapia et al, ; Cuevas et al, ; Dougherty, Wu, & Nichols, ; Nimmrich & Ebert, ; Peña et al, ; Ting, Kelley, Lambert, Cook, & Sullivan, ) and postsynaptic levels (Dinamarca, Ríos, & Inestrosa, ; Gylys et al, ; Harigaya, Shoji, Shirao, & Hirai, ; Hatanpaa, Isaacs, Shirao, Brady, & Rapoport, ; Ting et al, ).…”
Section: Introductionmentioning
confidence: 99%